A Proposal Of Nitrogen Balance In A Very High Density Olive Orchard - Belguerri, H.; Villar, J.m.; Pascual, M.; Fatmi, A.; Amadeu, A.; Rufat, J. (University of Eloued جامعة الوادي, 2016)
The nitrogen (N) balance was estimated in a very high density olive orchard in north- east of Spain, in order to calculate the inputs and outputs of N related to tree response and soil nitrogen availability. The calculate N inputs and outputs showed that N exported by yield and pruning material were higher for fertilized plots than unfertilized ones, and no significant differences were recorded for nitrogen mineralization between both treatments. N balance, defined as the difference between inorganic N content in soil at the end and the beginning of each year, was positive for both treatments but when vegetative growth and olive yield were compared, fertilized plots showed higher values, So it is wrong noting that a positive N balance in both case means that olive tree will provide a peak yield and vegetative growth but it is an adaptation of the olive trees to different soil N availability conditions by equilibrating their vegetative growth and fruit yield.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Mineralization; N exported by pruning material; N exported by crop; Fertilization; Fruit yield; Vegetative growth.